2018
DOI: 10.1111/1471-0528.15326
|View full text |Cite
|
Sign up to set email alerts
|

Portable Pocket colposcopy performs comparably to standard‐of‐care clinical colposcopy using acetic acid and Lugol's iodine as contrast mediators: an investigational study in Peru

Abstract: The Pocket colposcope performance was similar to that of a standard-of-care colposcope when identifying cervical lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Biases in the design of the included studies make interpretation of the ndings uncertain. First, there was a high risk of partial veri cation bias in three of ve studies [29,31,32], where less than 90% of index test recipients received the reference standard. Partial veri cation can result in overestimation of both sensitivity and speci city if women with more subtle disease are not identi ed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biases in the design of the included studies make interpretation of the ndings uncertain. First, there was a high risk of partial veri cation bias in three of ve studies [29,31,32], where less than 90% of index test recipients received the reference standard. Partial veri cation can result in overestimation of both sensitivity and speci city if women with more subtle disease are not identi ed.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, more than 90% of women who had received the index test also received the reference standard. In contrast, in Mueller et al, 63% of women received biopsy [32], in Nessa et al, 25% of women received biopsy [31], and in Newman et al, only 6% of women received a biopsy [29]. Conduct of the reference standard was problematic in two studies due to incorporation bias, where investigators use the index test to determine the need for reference standard and nal diagnosis [31,33].…”
Section: Quality Assessmentmentioning
confidence: 95%
See 1 more Smart Citation
“…3. The Pocket colposcope used in this study is unique compared to other colposcopes in its ability to acquire an image an inch away from the cervix, remove a majority of the noise (speculum, vaginal walls), and consequently decrease the level of image processing complexity required for cervix segmentation, which has been documented in previous methods [9][10][11]. When combined with the algorithms introduced here, the Pocket colposcope could enable widespread scalable screening for cervical cancer.…”
Section: Study Goalmentioning
confidence: 99%
“…Our group has developed a low-cost, portable, pointof-care digital colposcope, called the Pocket colposcope, to replace VIA with high-quality colposcopy, which is the established standard-of-care for triage in high-resource settings [9][10][11]. An international study conducted by our group found high concordance between the Pocket colposcope and standardof-care clinical colposcopes [12].…”
Section: A Backgroundmentioning
confidence: 99%